The Impact of the Jewish Lobby on the US Political Discourse - MESTOUR, MANNOUBIA; REMITA, AICHA (University of Eloued جامعة الوادي, 2024)
This dissertation aims to investigate the influence of Israeli lobby on the U.S. foreign policy under President Joe Biden administration. It elaborates the strategies used by the Israeli lobby to influence the U.S. foreign policy especially the policy towards Israeli-Palestinian conflict. One of the ways used by the Israeli lobby to influence the U.S. foreign policy is lobbying the Executive and legislative branches . The lobby is so powerful, it could even decide the President and Congress candidates who will sit on the important position in the U.S. government as well as decision-maker position ; consequently , the lobby process would be easier. Analysis reveals that political discourse frequently aligns with the interests of these groups often emphasizes support for Israel's security and framing the conflict in ways that favor Israeli perspectives. This alignment is evident in the rhetoric of major political parties, legislative initiatives and executive actions. The study finds that this influence extends beyond policy-making to affect media representation and public debate. Moreover, The lobbying efforts contribute to a dominant narrative that marginalizes Palestinian voices and perspectives, thereby influencing the broader public's understanding of the conflict. These findings highlight the complex interplay between lobbying activities and political discourse and suggest that the Jewish lobby plays a crucial role in shaping U.S. positions on the Israel-Palestine conflict. تسعى هذه الدراسة لتسليط الضوء على تأثير اللوبي الإسرائيلي على السياسة الخارجية الأمريكية خلال عهدة الرئيس جو بايدن من خلال شرح الاستراتيجيات التي يستخدمها اللوبي الإسرائيلي للتأثير على السياسة الخارجية للولايات المتحدة وخاصة السياسة تجاه الصراع الإسرائيلي الفلسطيني. إحدى الطرق التي يستخدمها اللوبي الإسرائيلي للتأثير على السياسة الخارجية للولايات المتحدة كالضغط على السلطتين التنفيذية والتشريعية. ونظرًا لأن اللوبي قوي للغاية، فيمكنه أيضًا تحديد مرشحي الرئيس والكونغرس الذين سيشغلون منصبًا مهمًا في الحكومة الأمريكية بالإضافة إلى منصب صانع القرار، وبالتالي فإن عملية الضغط ستكون أسهل. ويكشف التحليل أن الخطاب السياسي يتماشى في كثير من الأحيان مع مصالح هذه المجموعات، وغالباً ما يؤكد على دعم أمن إسرائيل ويضع الصراع في إطار يصب في صالح وجهات النظر الإسرائيلية. ويتجلى هذا الاصطفاف في خطاب الأحزاب السياسية الكبرى، والمبادرات التشريعية، والإجراءات التنفيذية. علاوة على ذلك، توصلت الدراسة إلى أن هذا التأثير يمتد إلى ما هو أبعد من صنع السياسات ليؤثر على التمثيل الإعلامي والنقاش العام. وتساهم جهود الضغط في خلق خطاب مهيمن يهمش الأصوات ووجهات النظر الفلسطينية، وبالتالي يؤثر على فهم الجمهور الأوسع للصراع. تسلط هذه النتائج الضوء على التفاعل المعقد بين أنشطة الضغط والخطاب السياسي، مما يشير إلى أن اللوبي اليهودي يلعب دورًا حاسمًا في تشكيل المواقف الأمريكية بشأن الصراع الإسرائيلي الفلسطيني.
Analysis of President Biden’s Speeches on the Israeli-Palestinian Conflict
Literature and Civilization
Keywords: Foreign policy; Israel; Jewish lobby; Middle East; Palestine; United States.; السياسة الخارجية، إسرائيل، اللوبي اليهودي، الشرق الأوسط، الولايات المتحدة الأمريكية.